Come, see the world with me ! - Wong, Philip (Philip Wong Pak Ming/Lee Ming Press Sdn Bhd, 2021)
From a childhood fascination for travel to visiting over 100 countries to-date, housing developer Philip Wong has gone from the Arctic to the tip of Africa and South America, Australia and in between these extremes inside this book: he's planning for an Antarctic trip next.